Heartbeat evoked potentials in patients with post-traumatic stress disorder: an unaltered neurobiological regulation system?. Issue 1 (1st January 2021) - Schmitz, Marius; Müller, Laura E.; Seitz, Katja I.; Schulz, André; Steinmann, Sylvia; Herpertz, Sabine C.; Bertsch, Katja
ABSTRACT: Background: Early life maltreatment is a risk factor for psychiatric disorders, including post-traumatic stress disorder (PTSD). Post-traumatic stress disorder is a severe and heterogeneous disorder with fluctuating states of emotional over- and undermodulation, including hypervigilance, dissociation, and emotion regulation deficits. The perception and regulation of emotions have been linked to interoception, the cortical representation and sensing of inner bodily processes. Although first therapeutic approaches targeting bodily sensations have been found effective in patients with PTSD, and deficits in interoceptive signal representation have been reported in other trauma-related disorders, such as borderline personality disorder (BPD), the role of interoception remains largely unexplored for PTSD. Objective: The objective was to investigate the cortical representation of cardiac interoceptive signals in patients with PTSD and its associations with early life maltreatment, trait dissociation, and emotion dysregulation. Methods: Twenty-four medication-free patients with PTSD and 31 healthy controls (HC) completed a 5-min resting electrocardiogram (ECG) with parallel electroencephalogram (EEG). Heartbeat evoked potential (HEP) amplitudes as a measure for cortical representation of cardiac interoceptive signals were compared between groups and correlated with self-report questionnaires. Results: We did not find significantly different mean HEP amplitudes in patients with PTSD compared to HC, although HEPs of patients with PTSD were descriptively higher. No significant associations between mean HEP amplitudes and early life maltreatment, trait dissociation or emotion dysregulation were obtained within the groups. Conclusion: The current finding does not indicate deficits in interoceptive signal representation at rest in individuals with PTSD. Whether patients with PTSD show altered HEP modulations during emotion regulation tasks and might benefit from therapeutic approaches aiming at changing the perception of bodily signals, needs to be investigated in future studies. HIGHLIGHTS: Patients with PTSD did not show reduced, but descriptively higher, heartbeat-evoked potentials at rest which does not indicate deficits in interoceptive signal representation.